Political connections: a literature review approach - Fajar Kristanto Gautama Putra; Iman Harymawan (Universitas Hayam Wuruk Perbanas, 2021)
The aim of this study was to highlight the key finding of corporate politicalconnections research. This study used 61 previous studies related tocorporate political connections to develop a structured literature review. Itwas found that most studies were conducted in developing countries as theyprovided a unique institutional setting for conduct political connectionsresearch. In addition, a political connection is used as independentvariables and the previous studies focuses on three related topics, whichare corporate performance, corporate action, and loan and special rights.Literature review study become more important nowadays, as the numberof empirical quantitative research amount has been increased lately. Thisanalysis also has research and practical implementation for researcher,practitioners, and regulators.